Teachers' factors, self-efficacy and social desirability as correlates of ICT utilisation for stress management among secondary school teachers in Oyo State, Nigeria (2016)
The study examined correlates of information and communication technology utilization for stress management among secondary school teachers in Oyo State, taking an in-depth study of Ibadan North Local Government Area. A sample of 160 teachers were randomly selected from which an “Information and Communication Technology for Stress Management Questionnaire" r=0.73 was used to collect data. Findings of the study indicated a significant relationship r= 0.648, p<0.05 between teachers' attitude to and the use of ICT for stress management. Social desirability was significantly related to the use of ICT for stress reduction r= 00.68, p<0.05, while teacher computer self-efficacy (r=0.116, p>0.05) and teachers’ personal characteristics were not significantly related to the use of ICT for stress management among secondary school teachers r= -0.167, p>0.05. The outcome of the study revealed that secondary school teachers ’ attitude and social desirability among staff are functions of whether teachers will reject or adopt ICT for stress management activities at the secondary school level. It was recommended that teachers and the administrative staff in secondary schools should develop positive attitudes towards the use of smart devices especially for stress management.